The Implementation and the Impact of Attention Grabbers in Young Learners’ Classrooms: A Case Study - Michael Recard; Yolanda H. Nathania (TEKNOSASTIK, 2021)
Due to the importance of attention grabber in the classroom management for pre-service teachers, this study examines the implementation and impact of attention grabbers in young learners’ classroom. The scope of this study focuses on pre-service teachers of the English Department in one University in Jakarta from grade two to five, and to attention grabbers which are produced when students are noisy and moving around the class while the teacher is giving instruction or explanation. The data were gathered from observation and video recording. The results indicated that the pre-service teachers still need to be aware to use attention grabbers when the classroom situation is not conducive. In order to make attention grabber become more effective when the teachers use attention grabbers in the classroom, it is important to make sure all of the students are responding to the attention grabbers. Furthermore, the suggestion for the next study is to find more participants in different grades.